Media and politics: a study among youth in Malaysia - A.Manaf, Aini Maznina; Syed Abdullah Idid, Syed Arabi; Buyong, Mazni; Ahmad, Zeti Azreen; Mohamed, Shafizan; Ahmad, Che Mahzan; Tengku Mohd Azzman, Tengku Siti Aisha; Baharum, Amran (2015)
Media have a tendency to shape youth’s opinion on politics and election. The exposure of youth to media is more likely to change their opinions towards political issues that are widely covered in the media. This paper discusses media usage patterns among youth in Malaysia and their particpation in politics and election. A study using focus groups with Malaysian youth was carried out in June 2015. The purpose of the study was to examine how media influence perception of youth in Malaysia in relation to politics and election. Using purposive sampling, the study employed focus group to examine how and why youth use media to understand about politics and election. Findings indicated that youth mostly rely on new rather than traditional media to get updated with political news. Facebook and whatsapp are among the two channels that they mainly utilised to gain information about politics.